Revision of the Oriental species of the genus Sphegina Meigen, 1822 (Diptera: Syrphidae) - Van Steenis Jeroen; Hippa Heikki; Mutin Valeri A. (MUSEUM NATL HISTOIRE NATURELLE, 2022)
The Oriental species of the genus Sphegina Meigen, 1822 are revised. The following 43 new species are described: Sphegina (Sphegina) abbreviata sp. nov. (Nepal), S. (S.) angustata sp. nov. (Nepal), S (Asiosphegina) albolobata sp. nov. (Vietnam), S. (Asiosphegina) amplistylus sp. nov. (Philippines), S. (A.) atrimanus sp. nov. (Vietnam), S. (A) bifida sp. nov. (Sabah, Malaysia), S. (A) bracon sp. nov. (Vietnam), S. (A.) brevipilis sp. nov. (China), S. (A) clavigera sp. nov. (Vietnam), S. (A) collicola sp. nov. (Malaysia), S. (A.) crinita sp. nov. (Java, Indonesia; Malaysia), S. (A.) dentata sp. nov. (Taiwan), S. (A.) distincta sp. nov. (Vietnam), S. (A.) exilipes sp. nov. (Java, Indonesia), S. (A.) farinosa sp. nov. (Sabah, Malaysia), S. (A.) fimbriata sp. nov. (Thailand), S. (A.) furcillata sp. nov. (Vietnam), S. (A.) ghatsi sp. nov. (India), S. (A.) gigantea sp. nov. (China), S. (A.) granditarsis sp. nov. (China), S. (A) hamulata sp. nov. (India), S. (A) hauseri sp. nov. (Nepal), S. (A.) incretonigra sp. nov. (Vietnam), S. (A.) inflata sp. nov. (Philippines), S. (A) inventum sp. nov. (Sabah, Malaysia), S. (A.) karnataka sp. nov. (India), S. (A.) licina sp. nov. (Thailand), S. (A) lobulata sp. nov. (Vietnam), S. (A.) lucida sp. nov. (Vietnam), S. (A) nigrotarsata sp. nov. (Vietnam), S. (A.) nubicola sp. nov. (Thailand), S. (A.) ornata sp. nov. (China), S. (A.) perlobata sp. nov. (Taiwan), S. (A.) plautus sp. nov. (China), S. (A.) prolixa sp. nov. (Malaysia, Thailand), S. (A.) setosa sp. nov. (Nepal, India), S (A.) spathigera sp. nov. (Philippines), S (A) spenceri sp. nov. (Vietnam), S (A.) strigillata sp. nov. (Vietnam), S. (A) taiwanensis sp. nov. (Taiwan), S. (A.) umbrosa sp. nov. (China), S. (A) verrucosa sp. nov. (Vietnam) and S. (A) vietnamensis sp. nov. (Vietnam). Sphegina. (A.) tenuis Brunetti, 1915 is not a synonym of S. (A.) javana de Meijere, 1914. The males of S (A.) apicalis Shiraki, 1930, S (A.) tricoloripes Brunetti, 1915 and S. (A.) varidissima Shiraki, 1930 and the females of S (A.) achaeta Hippa, van Steenis & Mutin, 2015, S. (A.) index Hippa, van Steenis & Mutin, 2015, S. (A.) mirifica Hippa, van Steenis & Mutin, 2015 and S. (S.) quadriseta Huo & Ren, 2006 are described for the first time. Sphegina (5) quadriseta is recorded for the first time in the Oriental region. A key to all the Oriental species of Sphegina is provided. The Oriental fauna of Sphegina now comprises 94 species.